2021
DOI: 10.1177/21677026211004582
|View full text |Cite
|
Sign up to set email alerts
|

Extending Expectancy Theory to Food Intake: Effect of a Simulated Fast-Food Restaurant on Highly and Minimally Processed Food Expectancies

Abstract: Unhealthy diets are widespread and linked to a number of detrimental clinical outcomes. The current preregistered experiment extended expectancy theory into the study of food intake; specifically, we tested whether a fast-food restaurant affects food expectancies, or the emotions one expects to feel while eating highly processed foods (e.g., pizza) and minimally processed foods (e.g., carrots). Participants ( N = 200, mean age = 18.79 years) entered a simulated fast-food restaurant or a neutral space, complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Participants were recruited August 11th–12th, 2020 via Amazon’s Mechanical Turk for “A Study on Advertisements and Beliefs” in which they would, “watch and rate the effectiveness of four short advertisement clips and complete some questionnaires about beliefs, feelings, and typical behaviors.” A power analysis conducted in G*Power Version 3.1.9.6 with the following parameters determined a sample size of 788 participants: one-way analysis of variance (ANOVA) with four groups, power = 0.90, α = 0.05, and a small expected effect size (Cohen’s d = 0.29). The expected effect size was based on prior work demonstrating exposure to a simulated fast-food restaurant increased positive highly-processed food expectancies ( Cummings et al, 2021 ). The power analysis yielded a sample size of 608 but, due to available research funds, 180 participants were added to mitigate anticipated non-compliance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were recruited August 11th–12th, 2020 via Amazon’s Mechanical Turk for “A Study on Advertisements and Beliefs” in which they would, “watch and rate the effectiveness of four short advertisement clips and complete some questionnaires about beliefs, feelings, and typical behaviors.” A power analysis conducted in G*Power Version 3.1.9.6 with the following parameters determined a sample size of 788 participants: one-way analysis of variance (ANOVA) with four groups, power = 0.90, α = 0.05, and a small expected effect size (Cohen’s d = 0.29). The expected effect size was based on prior work demonstrating exposure to a simulated fast-food restaurant increased positive highly-processed food expectancies ( Cummings et al, 2021 ). The power analysis yielded a sample size of 608 but, due to available research funds, 180 participants were added to mitigate anticipated non-compliance.…”
Section: Methodsmentioning
confidence: 99%
“…A power analysis conducted in G*Power Version 3.1.9.6 with the following parameters determined a sample size of 788 participants: one-way analysis of variance (ANOVA) with four groups, power = 0.90, α = 0.05, and a small expected effect size (Cohen's d = 0.29). The expected effect size was based on prior work demonstrating exposure to a simulated fast-food restaurant increased positive highly-processed food expectancies (Cummings et al, 2021). The power analysis yielded a sample size of 608 but, due to available research funds, 180 participants were added to mitigate anticipated non-compliance.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that expectancy theory can be used in various contexts beyond the workplace, for example, in investigating pro‐environmental behavior (Kiatkawsin & Han, 2017), tourism and hospitality (Abrate et al, 2021), consumer boycotts (Barakat & Moussa, 2017), and food consumption (Talwar et al, 2021). Cummings et al (2021) argued that translating principles from expectancy theory into food consumption is an emerging area of research that has potential to improve public health issues.…”
Section: Theoretical Foundationmentioning
confidence: 99%